Kecemasan Karier Mahasiswa Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten Ditinjau dari Jenis Kelamin - Ramanda, Peni (Indonesian Journal of Educational Counseling, 2023)
This study aims to describe: 1) the career anxiety level of FTK UIN SMH Banten students; 2) differences in career anxiety levels of FTK UIN SMH Banten students based on gender. 3) efforts to provide guidance and counseling services to reduce career anxiety for FTK UIN SMH Banten students. This study used a comparative quantitative method by comparing the career anxiety level of FTK UIN SMH Banten students based on gender. Data was collected with the Student Career Anxiety Scale (SKKM) and processed using an independent sample t-test. The results of the study revealed: (1) career anxiety of FTK UIN SMH Banten students is in the moderate category or score at 46.23; (2) There is a significant difference between the career anxiety of male and female students at FTK UIN SMH Banten with a significant level of 0.00; (3) Some of the efforts to reduce career anxiety of FTK UIN SMH Banten students are: group counseling or individual counseling. For preventive efforts, counselors in providing career guidance services such as group guidance, classical guidance, indirect services and the use of Islamic methods.